Comparison of a new high‐resolution monolithic column with core‐shell and fully porous columns for the analysis of retinol and α‐tocopherol in human serum and breast milk by ultra‐high‐performance liquid chromatography†. Issue 14 (21st June 2013) - Kučerová, Barbora; Krčmová, Lenka; Solichová, Dagmar; Plíšek, Jiří; Solich, Petr
<x xml:space="preserve">Abstract</x> The reduction of analysis time, cost, and improvement of separation efficiency are the main requirements in the development of high‐throughput assay methods in bioanalysis. It can be achieved either by ultra‐high‐performance liquid chromatography (UHPLC) using stationary phases with small particles (<2 μm) at high back pressures or by using opposite direction—monolithic stationary phases with low back pressures. The application of new types of monolithic stationary phases for UHPLC is a novel idea combining these two different paths. The aim of this work was to test the recently introduced second‐generation of monolithic column Chromolith® HighResolution for UHPLC analysis of liposoluble vitamins in comparison with core‐shell and fully porous sub‐2 μm columns with different particle sizes, column lengths, and shapes. The separation efficiency, peak shape, resolution, time of analysis, consumption of mobile phase, and lifetime of columns were calculated and compared. The main purpose of the study was to find a new, not only economical option of separation of liposoluble vitamins for routine practice.